Implementing EjtM3 (European Journal of Translational Myology, Mobility, Medicine) along the silk-road - Paola Arslan; Barbara Ravara (PAGEPress Publications, 2018)
Two main novelties will appear in the second 2018 Issue of the European Journal of Translational Myology demonstrating that the journal is vital and in expansion, one novelty is that the journal is implementing its authorship and readership to broader clinical fields from muscle myology and mobility to clinical medicine and surgery. Consequently, the Editorial Board is also expanding to allow a broader expert evaluation of Authors submitted typescripts. The expanded Editorial Board recently evaluated the option to change the name of the journal from Ejtm to EjtM3 (Myology, Mobility, Medicine), in order to expand the original journal title meaning. Another important novelty is the first BAM Seminal Paper by Damraurer et al. 18 (5): 139-148, 2008. It is now reprinted (with Basic and Applied Myology permission) in this Ejtm 28 (2), 2018. The topic (chemotherapy-induced muscle wasting) was up-dated by one of our Editors stressing the relevance of the BAM 2008 paper to focus attention not only of myologists, but also of oncologists. From 2008, BAM (renamed from 2010 European Journal of Translational Myology) went far beyond the limits of pure Myology. Al last, but hopefully not at least, a series of Rapid Reports from Iranian Authors are paving the pathway Venetia-extreme Orient, along the ancient silk-road. Ejtm will enthusiastically publish clinical activities from surrounding and extreme Orient. The Marco Polo tradition and his bravery seem successfully continuing.